Dry electrode film manufacturing method and manufacturing system

The method of applying polymer resin to the ends of electrode mixture powder and calendering to form uniform edges addresses the issues of uneven edges and material loss in dry electrode film manufacturing, enhancing the electrochemical performance and consistency of the films.

JP7667299B2Active Publication Date: 2025-04-22LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023553094
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-06
Filing Date
2022-08-04
Publication Date
2025-04-22
Estimated Expiration
2042-08-04

AI Technical Summary

Technical Problem

The manufacturing of dry electrode films for electrochemical devices faces challenges such as uneven edges, cracks, and material loss due to the calendering method, which affects the electrochemical performance and consistency of the batteries.

Method used

A method involving the preparation of electrode mixture powder and powdered polymer resin, followed by a crimping step where the polymer resin is applied to the ends of the electrode mixture powder, and then calendering to form a sheet with uniform edges, and finally removing the edge portions to achieve consistent width.

Benefits of technology

The resulting dry electrode film has uniform edges and consistent width, reducing material loss and improving handling and electrochemical performance by minimizing cracks and damage during the manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667299000002
    Figure 0007667299000002
  • Figure 0007667299000003
    Figure 0007667299000003
  • Figure 0007667299000004
    Figure 0007667299000004
Patent Text Reader

Abstract

The dry electrode film manufactured by the manufacturing method of the present invention has uniformly aligned edges, so that the dry electrode film can be controlled to a predetermined constant width. In addition, when a roll-to-roll continuous process is applied to the manufacture of the dry electrode film, the width of the dry electrode film can be controlled to a uniform width during the manufacture. In addition, since the width of the dry electrode film is easy to control, even when the dry electrode film is manufactured through different manufacturing batches, the difference in width of the dry electrode film between batches can be minimized. In addition, since the boundaries of the edges of the dry electrode film are uniform and constant, the rate of damage to the dry electrode film, such as the occurrence of cracks, is very low, making it easy to handle.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a dry electrode film to be used as an electrode for an electrochemical device, and also to a system for producing the dry electrode film.

[0002] This application claims priority to Korean Patent Application No. 10-2021-0104170, filed on August 6, 2021, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] As the use of fossil fuels increases rapidly, the demand for alternative energy and clean energy is increasing. As a part of this, the field of power generation and storage using electrochemistry is one of the most actively researched fields. A representative example of an electrochemical device using such electrochemical energy is currently a secondary battery, and the field of use is expanding. A representative example of such a secondary battery is a lithium secondary battery, which is not only used as an energy source for mobile devices, but is also used as a power source for electric vehicles and hybrid electric vehicles to replace vehicles that use fossil fuels such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution. In addition, the field of use is expanding as an auxiliary power source through gridization. The manufacturing process of such a lithium secondary battery is largely divided into three steps, namely, an electrode manufacturing process, an electrode assembly manufacturing process, and an aging process. The electrode manufacturing process is further divided into an electrode mixture mixing process, an electrode coating process, a drying process, a rolling process, a slitting process, a winding process, and the like. Among these, the electrode mixture mixing process is a process of blending components for forming an electrode active layer where an actual electrochemical reaction occurs in the electrode. More specifically, it is a process of mixing an electrode active material, which is an essential element of an electrode, other additives such as conductive materials and fillers, a binder for binding between powders and adhesion to a current collector, and a solvent for imparting viscosity and dispersing powders, to produce a fluid slurry.

[0004] The composition mixed for forming the electrode active layer is broadly called an electrode mixture. Then, an electrode coating process is performed in which the electrode mixture is applied onto an electrically conductive collector, and a drying process is performed to remove the solvent contained in the electrode mixture. The electrode is then rolled to a desired thickness.

[0005] Meanwhile, in the drying process, the solvent contained in the electrode mixture evaporates, which may induce defects such as pinholes and cracks in the already formed electrode active layer.In addition, the inside and outside of the active layer may not be dried uniformly, and a powder floating phenomenon may occur due to the difference in the evaporation speed of the solvent, i.e., the powder in the area that is dried first floats up and forms a gap with the area that is dried later, which may result in a deterioration in electrode quality.

[0006] In order to solve the above problems, a drying device capable of adjusting the evaporation rate of the solvent while uniformly drying the inside and outside of the active layer has been considered, but such a drying device is very expensive and requires considerable cost and time to operate, which is disadvantageous in terms of manufacturing process. Therefore, research into manufacturing dry electrodes that do not use a solvent has been actively conducted recently.

[0007] Dry electrodes are generally manufactured by laminating a free-standing dry electrode film, which is manufactured in the form of a film including an electrode active material, a binder, a conductive material, etc., on a current collector. The manufacturing process of such a dry electrode film includes a process of first mixing an electrode active material, a carbon material as a conductive material, and a fiberizable binder together in a blender, applying shear force through a process such as jet milling or kneading to fiberize the binder, and then calendering the resulting mixture into a film to manufacture a free-standing film.

[0008] However, when a dry electrode film is manufactured by applying a calendaring method to such a dry mixture, both ends in the cross-machine direction are not uniform, resulting in an uneven sawtooth shape, and the width dimension of the dry electrode film is not uniform, so that cracks are likely to occur from the gaps between the sawtooth shapes. FIG. 1 is a schematic diagram showing a method for manufacturing a conventional dry electrode film. Referring to this, an electrode mixture powder 11 is passed through a calendar roller 32 and compressed into a sheet shape to manufacture a dry electrode film 130. When such a dry electrode film is wound or unwound, such cracks may worsen and even lead to breakage of the dry electrode film, and if this is applied to the manufacture of a battery, the electrochemical performance of the battery may be significantly reduced. Meanwhile, even if such sawtooth portions are cut to make the boundaries of the dry electrode film uniform, the depth of the gullets of the sawtooth portions is not uniform, so that the width of the dry electrode film may not be uniform depending on the manufacturing batch. Furthermore, even in the case of dry electrode films manufactured in one production batch, the remaining portions are cut based on the minimum value of the ensured width, resulting in a large loss of electrode material.

[0009] Therefore, there is an urgent need to develop a dry electrode manufacturing technique that can solve these problems. Summary of the Invention [Problem to be solved by the invention]

[0010] In order to solve the above problems, the present invention has an object to provide a method for manufacturing a dry electrode film having uniformly aligned edges, and a manufacturing system for manufacturing the dry electrode film. [Means for solving the problem]

[0011] A first aspect of the present invention relates to a method for producing a dry electrode film for an electrochemical element, the method comprising the steps of: (S10) preparing an electrode mixture powder and a powdered polymer resin for manufacturing a dry electrode film; (S20) a pressing step in which the polymer resin is introduced into at least one end of the electrode mixture powder in the width direction, and then the electrode mixture powder and the polymer resin are pressed together to be processed into a sheet-like electrode member having a predetermined thickness; (S30) removing an edge portion having a predetermined width from at least one end in the width direction of the electrode member.

[0012] Here, the electrode member includes an electrode mixture portion having a predetermined width, and a protective portion having a predetermined width connected to an end portion of the electrode mixture portion in the width direction where the polymer resin is injected, and the protective portion is included in an edge portion of the electrode member and is removed in step S30.

[0013] According to a second aspect of the present invention, in the first aspect, the electrode mixture powder contains an electrode active material, a conductive material, and a binder resin, and the binder resin has been subjected to a fine fiberization process.

[0014] According to a third aspect of the present invention, in the first or second aspect, the step (S20) is performed by a calendaring process, and the polymer resin is input to both ends of an input stream of the electrode mixture powder during the calendaring process.

[0015] According to a fourth aspect of the present invention, in the third aspect, the calendaring step is performed by a pair of calendaring rollers, and the input flow of the polymer resin and the input flow of the electrode mixture powder are separated by a guide dam disposed in front of the calendaring rollers.

[0016] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the polymer resin is one that has been subjected to a fine fiber forming process.

[0017] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, the polymer resin contains an elastic polymer, and the elastic polymer is contained in an amount of 40% by weight or less with respect to 100% by weight of the polymer resin.

[0018] According to a seventh aspect of the present invention, in the sixth aspect, the elastic polymer includes at least one selected from styrene-butadiene rubber (SBR), butadiene rubber (BR), nitrile-butadiene rubber (NBR), fluorine-based rubber such as Viton (registered trademark) rubber, chloroprene rubber (CR), ethylene-propylene rubber (EPR), and silicone rubber.

[0019] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the polymer resin contains the same component as the binder resin contained in the electrode mixture powder.

[0020] According to a ninth aspect of the present invention, in the eighth aspect, the polymer resin is subjected to a fine fiberization process.

[0021] According to a tenth aspect of the present invention, in any one of the first to ninth aspects, the polymer resin contains polytetrafluoroethylene (PTFE).

[0022] According to an eleventh aspect of the present invention, in the tenth aspect, the polymer resin further comprises an elastomeric polymer.

[0023] According to the twelfth form of the present invention, in any one of the first to eleventh forms, the electrode mixture powder is produced by a method including: (a) a step of producing a powdered mixture containing an electrode active material, a conductive material, and a binder resin; (b) a step of kneading the powdered mixture at a temperature in the range of 70°C to 200°C to produce a mixture lump; and (c) a step of pulverizing the mixture lump to obtain the electrode mixture powder.

[0024] According to a thirteenth embodiment of the present invention, in the twelfth embodiment, the step (b) is carried out under a condition of atmospheric pressure or higher.

[0025] According to the 14th aspect of the present invention, in any one of the 1st to 13th aspects, in step (S20), the polymer resin is poured into both end portions of the electrode mixture powder in the width direction, and in step (S30), edge portions having a predetermined width are removed from both end portions of the electrode member in the width direction, and the protective portions are respectively connected to both end portions of the electrode mixture part in the width direction.

[0026] In addition, a fifteenth aspect of the present invention relates to an electrode for an electrochemical element, comprising a current collector and a dry electrode film disposed on one or both sides of the current collector, the dry electrode film being manufactured by the manufacturing method according to the first aspect.

[0027] A sixteenth aspect of the present invention relates to a secondary battery, the secondary battery comprising the dry electrode according to the fifteenth aspect, the dry electrode being a positive electrode, and an electrode assembly including the positive electrode, a negative electrode, and a separator is housed in a battery case together with a lithium-containing nonaqueous electrolyte.

[0028] According to a seventeenth aspect of the present invention, there is provided an energy storage device including the secondary battery according to the sixteenth aspect as a unit battery.

[0029] An eighteenth aspect of the present invention is a system for manufacturing a dry electrode film member, the system including: a blender for mixing electrode mixture raw materials including an active material, a conductive material, and a binder; a kneader for kneading the mixture to manufacture a mixture mass in order to fiberize the binder; a grinder for grinding the mixture mass to form an electrode mixture powder; and a calendar into which the electrode mixture powder and a polymer resin powder are introduced to form an electrode film member.

[0030] According to the 19th aspect of the present invention, in the 18th aspect, the calendar further includes a material supplying device, through which the electrode mixture powder and the polymer resin powder are fed, and the material supplying device further includes a partitioning member that divides the feeding path of the electrode mixture powder and the feeding path of the polymer resin powder.

[0031] The twentieth form of the present invention relates to an electrode film member for an electrochemical element, comprising: an electrode mixture powder for manufacturing a dry electrode film; and an edge portion in which a powdered polymer resin is pressed onto an end of the electrode mixture powder to form a sheet having a predetermined thickness. Effect of the Invention

[0032] The dry electrode film manufactured by the manufacturing method of the present invention has uniform edges, so that the dry electrode film can be controlled to a predetermined constant width. In addition, when a roll-to-roll continuous process is applied to the manufacture of the dry electrode film, the width of the dry electrode film can be controlled to a uniform width during manufacture. In addition, since the width of the dry electrode film is easy to control, even when the dry electrode film is manufactured through different manufacturing batches, the difference in width of the dry electrode film between batches can be minimized.

[0033] Furthermore, since the boundaries of the ends of the dry electrode film are uniform and consistent, the rate of damage to the dry electrode film, such as cracks, is very low, making it easy to handle. [Brief description of the drawings]

[0034] [Figure 1] 1 is a diagram illustrating a conventional method for manufacturing a dry electrode film and an edge boundary of a dry electrode film manufactured thereby. [Diagram 2] 1 is a photographic image of a dry electrode film prepared in Comparative Example 1. [Figure 3a] 1 is a schematic diagram illustrating a method for manufacturing a dry electrode film according to the present invention and an edge boundary of a dry electrode film manufactured thereby. [Figure 3b] 1 is a schematic diagram illustrating a method for manufacturing a dry electrode film according to the present invention and an edge boundary of a dry electrode film manufactured thereby. [Figure 4] 1 is a photographic image of the dry electrode film prepared in Example 1. [Diagram 5]FIG. 2 is a diagram showing a cut portion of a sample obtained from an example when evaluating mechanical properties. [Figure 6] FIG. 2 is a diagram showing a cut portion of a sample obtained from a comparative example when evaluating mechanical properties. [Figure 7] FIG. 2 is a diagram showing a cut portion of a sample obtained from a reference example when evaluating mechanical properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] The present invention will now be described in more detail to aid in understanding the present invention.

[0036] The terms and words used in this specification and claims should not be interpreted limited to their ordinary and dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of ​​the present invention, based on the principle that the inventor himself can appropriately define the concept of the term in order to explain the invention in the best possible way.

[0037] The terms used in this specification are used to describe exemplary embodiments and are not intended to limit the present invention. Unless otherwise specified, the singular expression includes the plural expression.

[0038] Furthermore, throughout the specification, when a part "comprises" another component, it does not mean excluding the other component, but means that the other component may be further included, unless otherwise specified.

[0039] The present invention relates to a method for manufacturing a free-standing dry electrode film and a system for manufacturing the same. The dry electrode film is manufactured by a dry manufacturing process as described below. In this specification, the term "free-standing" means that the film can maintain its independent shape without relying on other members and can be handled by itself.

[0040] Meanwhile, the dry electrode film may be applied to an electrode for an electrochemical device, such as a primary battery, an electric double layer capacitor, a supercapacitor, a fuel cell, a secondary battery, etc., and more specifically, the secondary battery may be a lithium ion secondary battery.

[0041] A first aspect of the present invention relates to a method for producing a dry electrode film.

[0042] In one embodiment of the present invention, the method for producing the dry electrode film includes: (S10) preparing an electrode mixture powder and a powdered polymer resin for manufacturing a dry electrode film; (S20) applying the polymer resin to at least one end of the electrode mixture powder in a width direction, and then compressing the electrode mixture powder and the polymer resin to be processed into a sheet-shaped electrode film member having a predetermined thickness; (S30) removing an edge portion having a predetermined width from at least one end in the width direction of the electrode film member.

[0043] Here, the electrode film member includes an electrode mixture portion having a predetermined width, and a protective portion having a predetermined width connected to an end portion of the electrode mixture portion in the width direction where the polymer resin is injected, and the protective portion is included in an edge portion of the electrode member and is removed in step S30.

[0044] Each stage is explained in more detail below.

[0045] First, an electrode mixture powder and a polymer resin for manufacturing a dry electrode film are prepared (S10). The electrode mixture and the polymer resin are each independently in the form of a powder that is an aggregate of a plurality of fine particles.

[0046] The electrode mixture powder is made of fine particles, and the fine particles include at least one or a mixture of two or more of an electrode active material, a conductive material, and a binder. In one embodiment of the present invention, the electrode mixture powder includes an electrode active material and a binder. The fine particles may have a particle diameter of 10 μm to 2,000 μm. When the particle diameter of the fine particles satisfies the above range, it is advantageous to form a film with uniform thickness and density and to ensure excellent physical properties. When the particle diameter is less than 10 μm, the fine particles are difficult to participate in film formation, such as by adhering to a roller during a calendaring process or being detached due to being poorly connected by binder fibers, and the mechanical strength may be reduced, which may impair the physical properties of the manufactured dry electrode film. On the other hand, when the particle diameter exceeds 2,000 μm, it is difficult to ensure the thickness uniformity of the dry electrode film.

[0047] In one embodiment of the present invention, the electrode mixture powder can be produced by the following method.

[0048] First, a mixture of an electrode active material, a conductive material, and a binder resin is prepared. In this case, the mixing for preparing the mixture is performed so that the electrode active material, the conductive material, and the binder resin are uniformly distributed, and since they are mixed in a powder form, they may be mixed by various methods without limitation as long as they can be simply mixed. However, in the present invention, since a dry electrode that does not use a solvent is prepared, the mixing may be performed by dry mixing, and the materials may be added to a general mixing device such as a mixer or blender.

[0049] The mixing may be performed using a mixer at 5,000 rpm to 20,000 rpm for 30 seconds to 2 minutes, more specifically at 10,000 rpm to 15,000 rpm for 30 seconds to 1 minute, in order to ensure uniformity of the resulting electrode mixture powder.

[0050] In the present invention, the binder resin is not limited to a specific one as long as it can be fiberized by the above-mentioned mixture preparation process and / or the fiberization step described below. The fiberization of the binder resin may be partially performed in the mixture preparation process, and may be finely fiberized in the fiberization step described below. The fiberization refers to a process of finely dividing a polymer, and may be performed using, for example, mechanical shear force. The fiberized polymer fiber has a surface that is melted to generate a large number of fine fibers (fibrils). Non-limiting examples of such binder resins include polytetrafluoroethylene (PTFE), polyolefin, or a mixture thereof, and more specifically, polytetrafluoroethylene (PTFE), and more specifically, polytetrafluoroethylene (PTFE). Specifically, the polytetrafluoroethylene (PTFE) may be included in an amount of 60 wt % or more based on the weight of the entire binder. Of course, in this case, the binder may further include at least one of polyethylene oxide (PEO), polyvinylidene fluoride (PVdF), polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP), and polyolefin-based binder resins.

[0051] The dry electrode may be a positive electrode, and the active material may be a positive electrode active material.

[0052] The positive electrode active material is not limited as long as it is in the form of a lithium transition metal oxide or a lithium metal iron phosphate compound, a metal oxide, for example, a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; 1+x Mn 2-x Lithium manganese oxides such as O4 (x=0~0.33), LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7; chemical formula LiNi 1-x M xNi-site type lithium nickel oxide represented by O2 (M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, x = 0.01 to 0.3); chemical formula LiMn 2-x M x Lithium manganese composite oxide represented by O2 (M = Co, Ni, Fe, Cr, Zn or Ta, x = 0.01 to 0.1) or Li2Mn3MO8 (M = Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of Li in the chemical formula is substituted with alkaline earth metal ions; lithium metal phosphate compound LiMPO4 (M = Fe, Co, Ni or Mn), disulfide compound; Fe2(MoO4)3 etc. are mentioned, but it is not limited thereto.

[0053] Alternatively, the dry electrode may be a negative electrode, and the active material may be a negative electrode active material. The negative electrode active material includes carbon such as graphitizable carbon and graphite-based carbon; Li x Fe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; silicon-based oxides such as SiO, SiO / C, SiO2; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials etc. may be used.

[0054] However, the dry electrode may specifically be a positive electrode, and thus, the active material may specifically be a positive electrode active material, and more specifically, it may be a lithium transition metal oxide, a lithium nickel-manganese-cobalt oxide, an oxide in which part of the lithium nickel-manganese-cobalt oxide is substituted with other transition metals, lithium iron phosphate, etc.

[0055] The conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity. For example, graphite such as natural graphite and artificial graphite; carbon blacks such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber and metal fiber; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used. More specifically, in order to uniformly mix the conductive material and improve conductivity, the conductive material may include one or more selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes, and more specifically, the conductive material may include activated carbon.

[0056] The mixture ratio of the active material, conductive material, and binder may be 80-98 wt %:0.5-10 wt %:0.5-10 wt %, more specifically, 85-98 wt %:0.5-5 wt %:0.5-10 wt %, of active material:conductive material:binder.

[0057] If the binder content is too high beyond the above range, the binder may be excessively fiberized in subsequent processes, which may affect the processes. If the binder content is too low, the binder may not be sufficiently fiberized, and may not be aggregated to form a mixture mass, making it difficult to produce a dry electrode film, or the physical properties of the dry electrode film may be deteriorated.

[0058] In addition, if the content of the conductive material is too high beyond the above range, the content of the active material is relatively reduced, resulting in a problem of a decrease in capacity. On the other hand, if the content is too low, sufficient conductivity may not be secured or the physical properties of the dry electrode film may be deteriorated, which is undesirable.

[0059] Meanwhile, depending on the case, a filler, which is a component that suppresses the expansion of the electrode, may be further added to the mixture. The filler is not particularly limited as long as it does not induce chemical changes in the battery and is a fibrous material, and for example, olefin polymers such as polyethylene and polypropylene; glass fiber, carbon fiber, and other fibrous materials may be used.

[0060] The mixture thus obtained is then subjected to a fiberization step for fiberizing the binder resin, which may involve high shear mixing (e.g., jet milling).

[0061] Alternatively, in one embodiment of the present invention, the fiberization step may be performed using a low shear kneading method, for example, using a kneader such as a kneader.

[0062] Such high shear mixing or kneading causes the binder to be fibrous, and the electrode active material and the conductive powder are bound or connected by the fibrous binder, so that a mixture mass having a solid content of 100% can be formed.

[0063] When the step of fiberizing the binder is performed by kneading, the kneading may be controlled at a speed of 10 rpm to 100 rpm. For example, the kneading may be controlled at a speed of 40 rpm or more or 70 rpm or less within the above range. The kneading may be performed for 1 minute to 30 minutes. For example, the kneading may be performed at a speed of 40 rpm to 70 rpm within the above range for 3 minutes to 7 minutes. Meanwhile, the kneading may be performed at a shear rate of 10 s -1 ~500s -1 In a specific embodiment of the present invention, the kneading may be performed for 1 minute to 30 minutes, and the shear rate may be controlled within a range of 30 s -1 ~100s -1 The range of the temperature can be controlled.

[0064] Moreover, the kneading step may be carried out under high temperature and pressure conditions equal to or higher than atmospheric pressure, more particularly under pressure conditions higher than atmospheric pressure.

[0065] More specifically, the kneading may be carried out at a temperature in the range of 50°C to 230°C, specifically, 90°C to 200°C.

[0066] If the temperature is lower than the above range, the binder will not be sufficiently fiberized during kneading and will not be sufficiently agglomerated during kneading, and film formation during calendaring will not be smooth. If the temperature is too high, the binder will be rapidly fiberized, and then the already formed fibers will be cut by excessive shear force, which is undesirable.

[0067] In addition, the kneading may be performed at atmospheric pressure or higher, specifically at a pressure of 1 atm to 3 atm, more specifically at 1.1 atm to 3 atm. If the kneading is performed at a pressure that is too high outside the above range, excessive shear force and pressure may be applied, causing problems such as cutting the formed fibers or excessively increasing the density of the mixture mass, which is undesirable. That is, according to the present invention, the intended effect of the present invention can be achieved when a low shear mixing process is performed at high temperature and pressure conditions higher than atmospheric pressure, instead of high shear mixing.

[0068] Next, the mixture mass produced through the kneading step is pulverized again to obtain a powdered electrode mixture.

[0069] The mixture lump produced through the kneading may be immediately calendered, but in this case, the mixture lump needs to be pressed under high pressure and high temperature to be made into a thin film, which may result in an excessively high density of the film or an inconsistent film. Therefore, the mixture lump produced as above is pulverized to produce a powdered electrode mixture.

[0070] In this case, the grinding may be performed using equipment such as, but not limited to, a blender or grinder, specifically, at a speed of 5,000 rpm to 20,000 rpm for 30 seconds to 10 minutes, more specifically, at a speed of 10,000 rpm to 18,000 rpm for 30 seconds to 1 minute.

[0071] If the rpm is too low or the grinding time is too short outside the above range, grinding will not be sufficient and powder of a size unsuitable for film formation may be produced, whereas if the rpm is too high or the grinding time is too long, a large amount of fine powder may be generated from the mixture mass, which is undesirable.

[0072] Meanwhile, when the binder fiberization is performed in the mixing step, a separate pulverization process may not be performed.

[0073] In the electrode mixture powder obtained by the above method, the binder resin is entirely or at least partially fiberized and divided by mechanical shearing force, etc., and in particular, the fiberized part on the surface of the binder resin is dissolved to generate a large number of fine fibers (fibrils). Therefore, among the fine particles obtained by the above method, the binder resin and the electrode active material particles are bonded to each other, and the bond can be further strengthened by the fine fibers of the binder resin.

[0074] Meanwhile, the polymer resin contained in the protective part may be any resin used for a dry electrode film, and is not limited to a specific component. In one embodiment of the present invention, the polymer resin may include at least one selected from a fluorine-based resin, a polyolefin-based resin, and a polyethylene oxide. The fluorine-based resin may include at least one selected from polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), and polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP). The polyolefin-based resin may include at least one selected from polyethylene, polypropylene, and polybutylene.

[0075] In addition, in one embodiment of the present invention, the polymer resin may further include an elastic polymer. Such an elastic polymer may include at least one selected from styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile butadiene rubber (NBR), fluororubber such as Viton® rubber, chloroprene rubber (CR), ethylene propylene rubber (EPR), and silicone rubber. If the protective part contains an excessive amount of elastic polymer, it is difficult to form it into a film. In consideration of this, the elastic polymer may not be contained relative to 100% by weight of the polymer resin, or, if contained, may be contained in a range of 40% by weight or less.

[0076] In an embodiment of the present invention, the polymer resin may be subjected to a microfiberization process. The microfiberization process may be performed by using a high shear mixing method or a low shear kneading method, as in the case of preparing an electrode mixture.

[0077] In one specific embodiment of the present invention, the polymer resin preferably contains polytetrafluoroethylene (PTFE), and more preferably contains 60% by weight or more of PTFE relative to 100% by weight of the polymer resin.

[0078] Meanwhile, in a specific embodiment of the present invention, the polymer resin may contain at least one component that is the same as the binder resin contained in the electrode mixture, in which case, when pressure is applied in a manufacturing process of the electrode member described below, the tensile modulus of the electrode part and the tensile modulus of the protective part become similar, thereby reducing the frequency of cracks or defects occurring between the electrode part and the protective part.

[0079] Thereafter, the prepared electrode mixture and polymer resin are compressed to manufacture an electrode film member. The electrode film member may be provided in a sheet form having a predetermined thickness. In one embodiment of the present invention, the electrode film member may be manufactured by a roll-to-roll continuous process and may be in a strip form having an aspect ratio exceeding 1. In one embodiment of the present invention, the thickness of the electrode film member may be 50 μm to 300 μm.

[0080] In one embodiment of the present invention, the electrode film member of step (S20) may be manufactured by a calendaring method in which the electrode mixture powder and the polymer resin powder are supplied to a calendar, and the supplied materials are thermocompressed using a roll press included in the calendar. In this case, the electrode mixture powder and the polymer resin powder may be supplied to the calendar roll through separate input paths. For example, the input path of the polymer resin powder may be set at one end or both ends of the input path of the electrode mixture powder. In this case, it is preferable to input the material so that the protective part and the electrode mixture part are connected to each other in the obtained electrode film member and do not separate from each other. Therefore, it is preferable that the input path is divided at the front stream of the calendar, and the boundaries of the material inputted to the calendar are overlapped to connect the protective part and the electrode mixture part. The input path may be divided by disposing a partition member for dividing the input path in the front stream of the calendar roll. 3a and 3b, a supply unit 31 having a guide dam 33 and a partition member 34 as such a partition member is provided in front of a calender roller 32, and the dam separates an input path for the polymer resin 12 from an input path for the electrode mixture powder 11. However, when the material is input to the calender roll after passing through the dam, the boundaries may overlap, and as a result, an electrode film member 150 in which an electrode mixture portion 152 and a protective portion 151 are connected may be manufactured.

[0081] As described above, the polymer resin powder is fed into one or both ends of the electrode mixture powder feeding path (feed flow) at the outside, so that an electrode member having a protective part disposed at one or both ends in the width direction of the electrode mixture part can be manufactured. The electrode mixture part is a part mainly including the result of calendering the electrode mixture powder, and the protective part is a part mainly including the result of calendering the polymer resin powder. Here, the term "mainly" means that the content is 50 wt% or more. In one embodiment of the present invention, the electrode mixture part and the protective part may be connected to each other by calendering, and the boundary part may be unclear due to the mixture of the polymer resin and the electrode mixture powder.

[0082] In this way, when the electrode mixture powder is calendered, the polymer resin powder is introduced into both ends of the electrode mixture powder introduction path, so that the boundaries of the ends of the electrode mixture part are uniformly formed. This is because the polymer resin compressed together with the electrode mixture part at the end of the electrode mixture part acts as a dam, preventing the end of the electrode mixture part in the width direction from spreading into an uneven pattern due to compression. As the end of the electrode mixture part in the width direction has a uniform and constant boundary, it is possible to minimize the amount of the electrode mixture part removed in the subsequent edge removal process. In addition, the width dimension of the electrode mixture part is easily controlled by the protective part.

[0083] In addition, the protective part, which has higher elasticity and impact absorption rate than the electrode mixture part, is disposed to prevent damage such as breakage and cracks due to external force. Even if an uneven sawtooth portion occurs at the boundary of the electrode mixture part, the bend of the sawtooth is filled with the protective part to fix the shape, so the frequency of cracks due to bending can be reduced.

[0084] In one embodiment of the present invention, the electrode mixture powder and the polymer resin may be supplied to the calender roller through a material supplying device disposed in the front stream of the calender. FIG. 3a is a schematic diagram showing how a material is supplied to the calender roll through a material supplying device 31 to manufacture a dry electrode film. The material supplying device 31 may include a container for storing the material, a supplying unit for supplying the material from the outside into the container, and a discharging unit for supplying the material from the container to the calender. Meanwhile, the container may have a partition as a partitioning member 34 provided inside the container so that the electrode mixture powder and the polymer resin powder are separated from each other without being mixed together. In one embodiment of the present invention, the partition may extend to the discharging unit or be provided in front of the discharging unit.

[0085] In another embodiment of the present invention, the calender may be provided with a guide dam 33 in the front stream as described above together with or instead of the material input device, and the polymer resin and the electrode mixture may be separated by the guide dam and supplied to the calender rollers (FIG. 3b).

[0086] When the material is supplied to the calender roller, a sheet-shaped electrode film member is manufactured by heat pressing. At this time, the temperature of the roller may be controlled in the range of 50°C to 200°C. In one embodiment of the present invention, the calender includes a roll press unit in which two rollers are arranged facing each other, and the roll press unit may be arranged in a plurality of consecutive units. At this time, the roll press unit may be appropriately controlled so that the rotation speed ratio of the two rollers is within the range of 1:1 to 1:10, independently of each other. For example, in one or more roll press units, the rotation speed ratio of the two rollers may be controlled to a ratio of 1:1 to 1:3. The calendering process may be performed once or multiple times until the electrode member has a desired thickness.

[0087] Then, an edge portion having a predetermined width is removed from one end or both ends in the width direction of the obtained electrode film member (S30). In one embodiment of the present invention, the edge portion may include the entire protective portion, and may include a part of the electrode mixture portion if necessary to remove the entire protective portion. In another embodiment, the edge portion may include a part of the protective portion. In one embodiment of the present invention, the width of the edge portion may be adjusted to a level that allows a strip-shaped dry electrode film made of electrode mixture powder to be obtained by removing at least a part or all of the protective portion. The protective portion is removed by removing the edge portion, and a dry electrode film is obtained from the electrode film member. The obtained dry electrode film may be in the form of a strip having a constant width and an aspect ratio exceeding 1. In addition, after the edge portion is cut and removed, the edge of the dry electrode film has a low roughness and a constant boundary. Meanwhile, in the present invention, the removal of the edge portion is not limited to a specific method, and a commonly used cutting means such as a cutting device equipped with a cutting blade made of metal or diamond material or a laser etching device may be applied.

[0088] Meanwhile, in the present invention, the dry electrode film may have a porosity of 20 vol% to 50 vol%, and may be controlled within the above range, preferably to a value of 40 vol% or less or 35 vol% or less. When the porosity satisfies the above range, it is desirable in terms of various effects. On the other hand, when the porosity is too small outside the above range, it is difficult for the electrolyte to be impregnated, which is undesirable in terms of life characteristics, output characteristics, etc., and when it is too large, it is undesirable in terms of energy density relative to volume, since the volume to achieve the same capacity increases. In one embodiment of the present invention, the porosity can be calculated by the following Equation 1 using the true density calculated based on the true density and composition of each component by measuring the apparent density of the dry electrode film.

[0089] [Formula 1] Porosity (%) = {1-(apparent density / true density)} x 100

[0090] Meanwhile, the present invention may further include a step of stacking the dry electrode film on one or both sides of a current collector and laminating the resultant to manufacture an electrode. The lamination may be a step of rolling the dry electrode film onto the current collector to attach it thereto. The lamination may be performed by a roll press method using a lamination roller, and in this case, the lamination roller may be maintained at a temperature of 20°C to 200°C.

[0091] Meanwhile, the current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In addition, the current collector may have fine irregularities on its surface to increase the adhesive force of the positive electrode active material, and may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0092] Furthermore, the current collector may be entirely or partially coated with a conductive primer to reduce resistance on the surface and improve adhesion. Here, the conductive primer may include a conductive material and a binder, and the conductive material may be, for example, a carbon-based material, as long as it is a conductive material. The binder may include a fluorine-based binder (including PVdF and PVdF copolymers), an acrylic binder, and a water-based binder that are soluble in a solvent.

[0093] The present invention also provides a secondary battery including the dry electrode, wherein the dry electrode is a positive electrode, and an electrode assembly including the positive electrode, the negative electrode, and a separator is housed in a battery case together with a lithium-containing nonaqueous electrolyte; and an energy storage device including the secondary battery as a unit battery.

[0094] Meanwhile, according to one embodiment of the present invention, there is provided a system for manufacturing a dry electrode film. The system may include a blender for mixing raw materials of an electrode mixture including an active material, a conductive material, and a binder, a kneader for kneading the mixture of the raw materials to manufacture a mixture mass, a pulverizer for pulverizing the mixture mass to form an electrode mixture powder, a calendar for forming the electrode mixture powder into a dry electrode film, a remover for removing an edge portion from the dry electrode film, and a lamination roll for positioning the dry electrode film on at least one side of a current collector and laminating the dry electrode film.

[0095] The blender is a mixer for mixing raw materials, and can mix the raw materials for the composite at a speed of 5,000 rpm to 20,000 rpm as described above. The kneader is a binder fiberizing device used in place of jet milling in the present invention, and can be used to make the mixture into a mixture mass through kneading. For this purpose, the kneader can be set to a temperature range of 70°C to 200°C and a pressure condition of normal pressure or higher.

[0096] The pulverizer is a device for pulverizing the mixture mass to form a powder for an electrode, and may be a blender or a grinder.

[0097] Meanwhile, for the calender and the remover, reference can be made to the above contents.

[0098] The lamination roll serves to attach the dry electrode film formed by the calendar onto at least one surface of a current collector and roll it.

[0099] The porosity of the dry electrode film according to the present invention can be determined by the calendar and lamination roll.

[0100] Meanwhile, in one embodiment of the present invention, the system may include a jet milling device instead of the kneader and the pulverizer. The specific structures of the blender, kneader, calendar, lamination roll, etc. are well known, so detailed description thereof will be omitted in this specification.

[0101] Hereinafter, the present invention will be described in detail with reference to examples, comparative examples, and experimental examples so that those skilled in the art can easily understand the present invention.

[0102] Example 1 Li(Ni x Co y Mn z Al a 94g of 100% ethylenediaminetetraacetate (100% ethylenediaminetetraacetate), 3g of carbon black as a conductive material, and 3g of polytetrafluoroethylene (PTFE) as a binder were put into a blender and mixed at 15,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was put into the kneader, and then operated at a speed of 50 rpm for 5 minutes to obtain a mixture mass. The mixture mass was put into a blender and pulverized at 10,000 rpm for 1 minute to obtain a mixed powder. PTFE was prepared as a polymer resin powder. Then, the mixed powder and the polymer resin powder were put into a wrap calender (roll diameter: 88 mm, roll temperature: 100°C, roll speed ratio 20 rpm / 24 rpm) to prepare an electrode film member. Figure 4 is a photographic image of the electrode film member manufactured in Example 1. The black parts are the electrode mixture parts, and the bright parts are the protective parts. From Figure 4, it can be seen that the boundaries of the ends of the electrode mixture parts are uniformly formed.

[0103] Example 2 The electrode film member obtained in Example 1 was subjected to a second lap calendaring process under the same conditions as the first process.

[0104] Example 3 94g of the positive electrode active material (same as in Example 1), 3g of carbon black as a conductive material, and 3g of polytetrafluoroethylene (PTFE) as a binder were put into a blender and mixed at 15,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was put into the kneader, and then operated at a speed of 50 rpm for 5 minutes to obtain a mixture lump. The mixture lump was put into a blender and pulverized at 10,000 rpm for 1 minute to obtain a mixed powder. A mixture of PTFE and SBR mixed in a weight ratio of 5:2 was prepared as a polymer resin powder. Then, the mixed powder and the polymer resin powder were put into a wrap calender (roll diameter: 88 mm, roll temperature: 100°C, roll speed ratio 20 rpm / 24 rpm) to prepare an electrode film member.

[0105] Example 4 The electrode film member obtained in Example 3 was subjected to a second lap calendaring process under the same conditions as the first process.

[0106] Example 5 94g of the positive electrode active material (same as in Example 1), 3g of carbon black as a conductive material, and 3g of polytetrafluoroethylene (PTFE) as a binder were put into a blender and mixed at 15,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was put into the kneader, and then operated at a speed of 50 rpm for 5 minutes to obtain a mixture lump. The mixture lump was put into a blender and pulverized at 10,000 rpm for 1 minute to obtain a mixed powder. A mixture of PTFE and fluorine-based rubber (Viton (registered trademark)) in a weight ratio of 5:2 was prepared as a polymer resin powder. Then, the mixed powder and the polymer resin powder were put into a wrap calender (roll diameter: 88 mm, roll temperature: 100°C, roll speed ratio 20 rpm / 24 rpm) to prepare an electrode film member.

[0107] Example 6 The electrode film member obtained in Example 5 was subjected to a second lap calendaring process under the same conditions as the first process.

[0108] Comparative Example 1 94 g of the positive electrode active material (same as in Example 1), 3 g of carbon black as a conductive material, and 3 g of polytetrafluoroethylene (PTFE) as a binder were put into a blender and mixed at 15,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150° C., and the mixture was put into the kneader, and then operated at a speed of 50 rpm for 5 minutes to obtain a mixture mass. The mixture mass was put into a blender and pulverized at 10,000 rpm for 1 minute to obtain a mixed powder. Then, the mixed powder was put into a wrap calender (roll diameter: 88 mm, roll temperature: 100° C., roll speed ratio 20 rpm / 24 rpm) to prepare a dry electrode film. FIG. 2 is a photographic image of the dry electrode film prepared in Comparative Example 1. According to FIG. 2, it can be seen that the boundary at the end of the dry electrode film is not aligned and is formed in a very uneven sawtooth pattern.

[0109] Comparative Example 2 The dry electrode film obtained in Comparative Example 1 was subjected to a second lap calendaring process under the same conditions as the first process.

[0110] Mechanical property evaluation The electrode film members (including protective parts) obtained in Examples 1 to 6 and the dry electrode films (without protective parts) obtained in Comparative Examples 1 and 2 were cut to a size of 1 cm x 7 cm. Each sample was tested according to the ASTM 638 method using a UTM device manufactured by ZwickRoell. In this experiment, the preload was 0.01 kg / cm and the speed was 50 mm / min. In addition, the breaking elongation of each sample was calculated by multiplying the length at break / initial sample length by 100. The experimental results are summarized in Table 1 below.

[0111] In the case of the embodiment, a 1 cm wide portion from one end of the electrode film member inward in the width direction was cut to a length of 7 cm to prepare a sample, and the 1 cm wide sample included a protective portion (see FIG. 5). In the case of the comparative example, a 1 cm wide portion from the end of the electrode film member inward, excluding the irregular sawtooth portion, was cut to a length of 7 cm to prepare a sample, and the irregular sawtooth portion was maintained (see FIG. 6). That is, the width of the sample was the width of the irregular sawtooth portion + 1 cm. Meanwhile, an electrode film was manufactured in the same manner as in Comparative Example 1, and then cut to a length of 7 cm on both sides of the 1 cm wide portion centered on the width center line (a) to prepare Reference Example 1, and an electrode film was manufactured in the same manner as in Comparative Example 2, and then cut to a length of 7 cm on both sides of the 1 cm wide portion centered on the width center line (a) to prepare Reference Example 2. The reference examples were prepared to show the mechanical strength of an electrode film manufactured without damage to the ends, and the measured values ​​were compared with those of the embodiment and comparative example as follows.

[0112] [Table 1]

[0113] From Table 1, it can be seen that the ends of the electrode film members obtained in the Examples have all superior mechanical properties compared to the ends of the electrode films obtained in the Comparative Examples. It was confirmed that the mechanical properties of the Comparative Examples were much lower than those of the Examples. Meanwhile, in the Examples, the mechanical strength of the ends was equal to or higher than that of the Reference Example. Therefore, it can be seen that in the case of the electrode film member having a protective part, the shape is stably maintained during the electrode manufacturing process, and the effect of improving processability is excellent. [Explanation of symbols]

[0114] 31: Material supply device 11: Electrode mixture powder 32: Calendar roller 130: Dry electrode film 12: Powdered polymer resin 33: Guide Dam 34: Partition material 151:Protection Department 152: Electrode mixture part 150: Electrode film material

Claims

1. (S10) preparing an electrode mixture powder and a powdered polymer resin for manufacturing a dry electrode film; (S20) adding the polymer resin to at least one end of the electrode mixture powder in the width direction, and then compressing the electrode mixture powder and the polymer resin to process the electrode mixture powder into a sheet-like electrode member having a predetermined thickness; (S30) removing an edge portion having a predetermined width from at least one end in a width direction of the electrode member, the electrode member includes an electrode mixture portion having a predetermined width, and a protective portion having a predetermined width connected to an end portion in a width direction of the electrode mixture portion where the polymer resin is injected, the protective portion being included in an edge portion of the electrode member and being removed in the step (S30).

2. The method for producing a dry electrode film according to claim 1 , wherein the electrode mixture powder contains an electrode active material, a conductive material, and a binder resin, and the binder resin has been subjected to a fine fiberization process.

3. The method for manufacturing a dry electrode film according to claim 1 , wherein the step (S20) is performed by a calendaring process, and the polymer resin is introduced into both ends of an input flow of the electrode mixture powder during the calendaring process.

4. 4. The method for producing a dry electrode film according to claim 3, wherein the calendaring step is performed by a pair of calendaring rollers, and the input flow of the polymer resin and the input flow of the electrode mixture powder are partitioned by a guide dam disposed in front of the calendaring rollers.

5. The method for producing a dry electrode film according to claim 1 , wherein the polymer resin is subjected to a fine fiberization process.

6. The polymer resin includes an elastic polymer, and the elastic polymer is included in an amount of 40% by weight or less based on 100% by weight of the polymer resin; 2. The method for producing a dry electrode film according to claim 1, wherein the elastic polymer comprises at least one selected from the group consisting of styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile butadiene rubber (NBR), fluorine-based rubber, Viton (registered trademark) rubber, chloroprene rubber (CR), ethylene propylene rubber (EPR), and silicone rubber.

7. The method for producing a dry electrode film according to claim 1 , wherein the polymer resin contains the same component as the binder resin contained in the electrode mixture powder.

8. The method for producing a dry electrode film according to claim 7 , wherein the polymer resin has been subjected to a fine fiberization process.

9. The method for producing a dry electrode film according to claim 1 , wherein the polymer resin comprises polytetrafluoroethylene (PTFE).

10. The polymer resin further comprises an elastomeric polymer; 10. The method for producing a dry electrode film according to claim 9, wherein the elastic polymer includes at least one selected from the group consisting of styrene butadiene rubber (SBR), butadiene rubber (BR), nitrile butadiene rubber (NBR), fluorine-based rubber, Viton (registered trademark) rubber, chloroprene rubber (CR), ethylene propylene rubber (EPR), and silicone rubber.

11. The electrode mixture powder is (a) producing a powdery mixture containing an electrode active material, a conductive material, and a binder resin; (b) kneading the powder mixture at a temperature in the range of 70°C to 200°C to produce a mixture mass; and (c) pulverizing the mixture lump to obtain an electrode mixture powder. The method for producing a dry electrode film according to claim 1 .

12. The method for producing a dry electrode film according to claim 11, wherein the step (b) is carried out under a pressure condition of 1 atm to 3 atm.

13. In the step (S20), the polymer resin is poured into both end portions of the electrode mixture powder in the width direction, In the step (S30), edge portions having a predetermined width are removed from both ends of the width direction of the electrode member, The method for producing a dry electrode film according to claim 1 , wherein the protective portion is connected to both end portions of the electrode mixture portion in a width direction.

14. 1. A system for manufacturing a dry electrode film member, comprising: a blender for mixing electrode mixture raw materials including an active material, a conductive material, and a binder to form a mixture; a kneader for kneading the mixture to produce a mixture mass in order to fiberize the binder; a grinder for grinding the mixture mass to form an electrode mixture powder; and a calender into which the electrode mixture powder and the polymer resin powder are introduced to form an electrode film member. The calendar further includes a material supplying device, and the polymer resin powder is supplied to at least one end of the electrode mixture powder in a width direction through the material supplying device.

15. The system according to claim 14 , wherein the material supplying device further includes a partition member that divides an input path for the electrode mix powder from an input path for the polymer resin powder.

16. An electrode mixture powder for producing a dry electrode film; and an edge portion in which a powdered polymer resin is compressed onto an end portion of the electrode mixture powder to form a sheet having a predetermined thickness.

Citation Information

Patent Citations

  • Manufacturing method of electrode

    JP2018186033A

  • Dry electrode manufacture by temperature activation method

    JP2020196887A

  • Compositions and methods for dry electrode films having reduced binder content

    WO2019222110A1